The The Effectiveness of REALIA as a Medium for Writing Descriptive Text - Ratu Yulianti Natsir (Celebes Scholar pg, 2023)
The goal of this study was to see how effective Realia was at writing descriptive text by the first semester of English at Unismuh Makassar. The sample for this study was drawn from two classes using the purposive sampling technique, with one group serving as the experimental class and the other as the control class, for a total sample of 30 students from the English Department at Unismuh Makassar's first semester. This study's instrument was a writing test. The researcher used a pre-test and a post-test to collect data. The researcher taught the descriptive text using realia. The researcher used the t-test to statistically analyze the data. The t - value was calculated to be 6.55. The t- table value was 2.00 based on the 0.05 significance level, and the computation revealed that the t- value was more significant than the t- table, which was 6.55>2.00. The effectiveness of realia can also be seen in the experimental and control groups' post-treatment scores. The experimental class's mean posttest score was 86.51, putting it in the very good category. The control group's mean posttest score was 76.54, putting it in the good category. The experimental group outperformed the control group, it is possible to conclude. Based on the t-test results, it can be demonstrated that using realia as a media in writing, specifically descriptive text for students, is a reference for teachers.